The Relationship between Eyestrain and the Occurrence of Floaters in Kalam Kudus Senior High School - Hambali, Nadya; Meriana Rasyid (Department of Opthalmology, Faculty of Medicine, Universitas Sriwijaya, 2023)
Introduction: Floaters, or particles that appear to float in the visual field, are often subjective complaints that cause disruptive sensations in vision. Eye strain, which is a common symptom associated with prolonged use of digital screens, can lead to other visual disorders. However, there is limited research examining the relationship between eye strain and floaters. This study aimed to evaluate the relationship between eyestrain and the occurrence of floaters in Kalam Kudus Senior High School. Methods: The study was conducted using a cross-sectional method with 62 respondents who extensively use electronic devices. Data on eye strain symptoms and the occurrence of floaters were collected using a standard questionnaire. Statistical analysis was performed to evaluate the relationship between eye strain and floaters. Results: The results of the study showed a significant relationship between eyestrain and the occurrence of floaters (p-value = 0.022). Students who reported eyestrain had a higher risk of experiencing floaters. Conclusion: Excessive use of digital screens and eye strain can contribute to the development of floaters in the high school student population.